Satisfaction of low-cost housing among B40 group / Muhamad Hazwan Aqif Ahmad Safiri and Mohd Nazri Abdullah - Ahmad Safiri, Muhamad Hazwan Aqif; Abdullah, Mohd Nazri (2020)
Low cost housing is a government initiative to b40 group or low income household to afford a house for shelter and overcome housing issues. The aim of the Public Housing System (PPR) is to ensure and provide a house for squatter-specific occupants, such as fires and individuals or families. However, the quality of low cost housing is facing problem such as poor management, defect on building, and others. This research attempts to examine the satisfaction towards the quality of low cost housing among b40 group. The first objective of this research is to identify the residents' level of satisfaction on low cost housing. The second objective is to identify factor influencing the dissatisfaction on quality of low cost housing. The third objective is to identify the effects of quality low cost housing towards residents' life. 50 questionnaires were collected on this survey from PPR Pangsapuri Simpang Perdana Taiping, Perak and PPR Rumah Pangsa Pasir Puteh, Ipoh, Perak. The collected data were analysed using descriptive statistics. The research on objective 1 shows that Surau is the most quality component that residents are very satisfied. The result of objective 2 shows that overall the majority of residents agree with the statement. The highest very agree statement is the size of the house which is too narrow on low cost housing. The result of objective 3 shows that overall most residents agree with the statement. The small space of house will affect resident's quality of life has most very agree vote. From this research, it can be concluded that the low cost housing must improve their housing policy and implementation to achieve government vision to provide affordable, comfortable, prosperous and good housing for residents.